Картографическая основа оперативной оценки природно-техногенных рисков и ущербов - Levkevich Виктор; Kryuchkov А.; Kasperov Георгий; Pastukhov Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Basic technical approaches used in natural and anthropogenic risks and damages forecasting based on gis-technologies and remote sensing data are reviewed.